Weight stigma and obesity‐related policies: A systematic review of the state of the literature. (9th September 2021) - Hill, Briony; Bergmeier, Heidi; Incollingo Rodriguez, Angela C.; Barlow, Fiona Kate; Chung, Alexandra; Ramachandran, Divya; Savaglio, Melissa; Skouteris, Helen
Summary: Weight stigma is an important issue colliding with obesity‐related policies; both have population health and social impacts. Our aim was to conduct a systematic review of the peer‐reviewed literature that combined the concepts of stigma, obesity, and policy. We searched PsycINFO, Medline, Scopus, and Google Scholar for peer‐reviewed articles amalgamating terms relevant to stigma, obesity, and policy. Of 3219 records identified, 47 were included in the narrative synthesis. Two key types of studies emerged: studies investigating factors associated with support for obesity‐related policies and those exploring policy implementation and evaluation. We found that support for nonstigmatizing obesity‐related policies was higher when obesity was attributed as an environmental rather than individual problem. An undercurrent theme suggested that views that blame individuals for their obesity were associated with support for punitive policies for people living in larger bodies. Real‐world policies often implicitly condoned stigma through poor language choice and conflicting discourse. Our findings inform recommendations for policy makers that broader socioecological stigma‐reduction approaches are needed to fully address the issue of weight stigma in obesity‐related policies. Efforts are needed in the research and policy sectors to understand how to improve the design and support of nonstigmatizing obesity‐related policies.